2016
DOI: 10.1109/jphotov.2016.2566887
|View full text |Cite
|
Sign up to set email alerts
|

Control of Crack Formation for the Fabrication of Crack-Free and Self-Isolated High-Efficiency Gallium Arsenide Photovoltaic Cells on Silicon Substrate

Abstract: We proposed a new scheme, controlling the crack formation by notch patterns, to fabricate self-isolated high-efficiency gallium arsenide (GaAs)-based solar cells on a silicon (Si) substrate. The notch patterns introduced into the Si substrate were found to successfully generate the crack-free areas of 2 mm × 2 mm size separated by the cracks for the 5.8-μm-thick GaAs layers on it. The individual solar cells on the crack-free areas were confirmed to be electrically isolated from one another by the well-defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Enhancing energy conversion efficiency is one of the most important issues in today's global solar photovoltaic (PV) technology in which great effort and research have been made toward achieving higher conversion efficiency at lower production cost . However, the majority of PV cell types, such as Si, CuIn x Ga 1− x Se y S 1− y (CIGS), Cu 2 ZnSnS 4− x Se x (CZTS), GaAs, CdTe, dye‐sensitized (DSSC), perovskite, and organic solar cells, still suffer from low external quantum efficiency (EQE) in the UV wavelength region due to surface reflection, scattering, and thermalization losses, which limit conversion efficiency . These losses are mostly caused by the energy difference between the incident UV photons (>3.2 eV) and bandgap of PV cells (1.0–1.6 eV) .…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing energy conversion efficiency is one of the most important issues in today's global solar photovoltaic (PV) technology in which great effort and research have been made toward achieving higher conversion efficiency at lower production cost . However, the majority of PV cell types, such as Si, CuIn x Ga 1− x Se y S 1− y (CIGS), Cu 2 ZnSnS 4− x Se x (CZTS), GaAs, CdTe, dye‐sensitized (DSSC), perovskite, and organic solar cells, still suffer from low external quantum efficiency (EQE) in the UV wavelength region due to surface reflection, scattering, and thermalization losses, which limit conversion efficiency . These losses are mostly caused by the energy difference between the incident UV photons (>3.2 eV) and bandgap of PV cells (1.0–1.6 eV) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the micro crack analysis on gallium arsenide (GaAs) PV solar cells has been carried out by S. Oh et al [12]. It was observed that the crack density, defined as the total length of the micro crack per unit area, is found to be in the range from 13.8 to 33.2 cm-1 in all investigated solar cell samples of 1620.…”
Section: Introductionmentioning
confidence: 99%
“…The examination have been carried out using 27 different PV modules using EL imaging method, where the extreme micro cracks found in the PV modules is parallel to busbars with 50% relative occurrence. Moreover, the current-voltage curve analysis based on gallium arsenide (GaAs) solar cells have been inspected by S. Oh et al [13]. It was evident that the yield voltage increases while decreasing the micro crack size.…”
Section: Introductionmentioning
confidence: 99%